Targeting Oxidative Stress and Inflammatory Response for Blood-Brain Barrier Protection in Intracerebral Hemorrhage - Chen, Shengpan; Li, Lingzhi; Peng, Chao; Bian, Chunjing; Ocak, Pinar Eser; Zhang, John H; Yang, Yong; Zhou, Dong; Chen, Guangzhong; Luo, Yumin (Antioxidants & redox signaling, 2022)
Blood-brain barrier (BBB) disruption is a major pathological change after intracerebral hemorrhage (ICH) and is both the cause and result of oxidative stress and of the immune response post-ICH. These processes contribute to ICH-induced brain injury. After the breakdown of cerebral vessels, blood components, including erythrocytes and their metabolites, thrombin, and fibrinogen, can access the cerebral parenchyma through the compromised BBB, triggering oxidative stress and inflammatory cascades. These aggravate BBB disruption and contribute to further infiltration of blood components, resulting in a vicious cycle that exacerbates brain edema and neurological injury after ICH. Experimental and clinical studies have highlighted the role of BBB disruption in ICH-induced brain injury. In this review, we focus on the strategies to protect the BBB in ICH. Specifically, we summarize the evidence and the underlying mechanisms, including the ICH-induced process of oxidative stress and inflammatory response, and we highlight the potential therapeutic targets to protect BBB integrity after ICH. Future studies should probe the mechanism of ferroptosis as well as oxidative stress-inflammation coupling in BBB disruption after ICH and investigate the effects of antioxidants and immunomodulatory agents in more ICH clinical trials.